Purification of bovine pancreatic glucagon as a by-product of insulin production - A.S.R. Andrade; L. Vilela; H. Tunes (Brazilian Journal of Medical and Biological Research, 1997)
A process for purifying bovine pancreatic glucagon as a by-product of insulin production is described. The glucagon-containing supernatant from the alkaline crystallization of insulin was precipitated using ammonium sulfate and isoelectric precipitation. The isoelectric precipitate containing glucagon was then purified by ion-exchange chromatography on Q-Sepharose FF, gel filtration on Sephadex G-25 and ion-exchange chromatography on S-Sepharose FF. A pilot scale test was performed with a recovery of 87.6% and a purification factor of 8.78 for the first chromatographic step, a recovery of 75.1% and a purification factor of 3.90 for the second, and a recovery of 76.2% and a purification factor of 2.36 for the last one. The overall yield was 50%, a purification factor of 80.8 was obtained and the fraction containing active glucagon (suitable for pharmaceutical preparations) was 84% pure as analyzed by HPLC